2012
DOI: 10.1590/s1516-89132012000600012
|View full text |Cite
|
Sign up to set email alerts
|

Growth curve and development of the internal calli structure of Eucalyptus camaldulensis Dehn

Abstract: The objective of this work was to elucidate the growth curve of Eucalyptus camaldulensis Dehn. calli analyzing their anatomical modifications. A sigmoid aspect of the growth curve of the calli fresh matter was observed, with five different phases (lag, exponential, linear, deceleration and decline). In the lag phase, the highest growth percentage 87%, was observed, which reduced during the evaluation period to 17% in the linear phase. As for the anatomical analyses, cellular multiplications was observed during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 21 publications
0
7
0
1
Order By: Relevance
“…Interestingly, a subset of four unknown proteins was strongly up-regulated by CAG in calli; At1G47400 and AT1G47395, described both as hypothetical proteins, At2G30766; belongs to cytochrome P450 family and AT1G13609 which seems to be part of Defensin-like (DEFL) family protein. The last two genes have also been proved that they are up-regulated under Fe deficiency stress conditions but in leaves [ 36 ]. Fe is known as a component of the photosystems and essential for photosynthesis.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a subset of four unknown proteins was strongly up-regulated by CAG in calli; At1G47400 and AT1G47395, described both as hypothetical proteins, At2G30766; belongs to cytochrome P450 family and AT1G13609 which seems to be part of Defensin-like (DEFL) family protein. The last two genes have also been proved that they are up-regulated under Fe deficiency stress conditions but in leaves [ 36 ]. Fe is known as a component of the photosystems and essential for photosynthesis.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, at the stationary phase, no weight increase of culture occurs, but the maximum accumulation of secondary metabolites occurs. Cellular death happens during the decline phase [ 46 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Growth curve revealed that specie displayed significant plasticity in growth rates across of the 30 days. The allocation of biomass to different plant organs depends on species, ontogeny, medium concentration and on the environment where of the explant growth (Mendonça et al, 2012;Chen, 2015). The effects of days were greater suggesting that just in the case of days, biomass allocation is an important factor in plant response to growth.…”
Section: Growth Curvementioning
confidence: 99%